Gender Roles against Opportunities for Entrepreneurship - Khoirul Umam (Journal of Business and Behavioural Entrepreneurship, 2017)
Micro, Small and Medium Business activities have a very important role in promoting the economy because this sector has been tested to have resistance to the economic crisis. Micro, Small and Medium Business has wide employment opportunities that can improve people's welfare. But the facts above are not as easy as Micro, Small and Medium Also has some problems, where small businesses Often face natural exa interest of ions with various Difficulties, such as capital constraints, human resources, changing government policies, business locations, competition, technological development, etc,. It is above the same set of money with entrepreneur. Being a successful entrepreneur is not easy to manifest, many things that need to be studied to be able to open the horizon, not only with expertise, hardwork without tenacy will be empty and include resistant to be disturbing temptations in business activity. Surely the above should have tricks or tips so that the goal in entrepreneurship to be successful. The above matter of course has an influence on the advance of entrepreneurship. Students are the embryo that has a good potential for realizing entrepreneurial activities. Successful entrepreneurial tips become the deciding factor of motivating students in entrepreneurship. Sample case studies have been conducted at Thamrin University.